Avaliação da prática de atividade física em escolares brasileiros e associação dessa prática com características individuais e contextuais - Luciano Antonacci Condessa (2018)
Introduction: Physical activity (PA) is one of the main protection factors against chronic non-communicable diseases, and its practice should be stimulated throughout the life cycle. In Brazil, fewer than 50% of adolescents practice PA regularly (300+ minutes/week), and few studies are evaluating PA practice over time in this age group, as well as the association of this practice with individual and contextual characteristics. Objectives: To evaluate the practice of PA in adolescents by comparing the surveys of the National Adolescent School-based Health Survey (PeNSE) of 2012 and 2015 (article 1), to investigate the association of this practice with individual characteristics (article 2) and with contextual characteristics (article 3). Methods: In the first article, the overall PA indicator (with cut-off point of 300+ minutes/week) was used to determine the prevalence of physically active adolescents in the PeNSE/2012 and PeNSE/2015 surveys. A stabilization was observed in the prevalence of physically active adolescents between 2012 (21.0%, 95% CI 20.3 - 21.7) and 2015 (20.7%, CI 95%: 20.1 - 21.3), regardless of sex, age, mother's schooling or skin color. This stabilization was also observed in all capitals, except for Belém, where a reduction was observed in the prevalence of physically active adolescents. In the second article, which used PeNSE/2012 data, the response variable was the regular practice of PA (determined by the overall PA indicator with the cut-off point of 300+ minutes/week) used to classify adolescents as active or insufficiently active. The explanatory variables were grouped into four domains: 1) Demographic; 2) Psychosocial; 3) Behavioral; 4) Sociocultural. In order to verify the factors associated with regular practice of PA, a Poisson regression stratified by sex was performed. The prevalence of physically active adolescents was higher in boys when compared to girls, 27.9% and 13.1%, respectively. A higher practice of PA was observed in boys who were younger in age, whose mothers had higher education levels, who consumed healthy foods such as beans, fruits, vegetables, and milk, as well as in boys who benefited from family supervision. At the same time, unhealthy habits such as insomnia and alcohol consumption were also positively associated with PA practice. In girls, a higher practice of PA was observed among those who lived with their mothers and whose mothers had higher education levels. In addition to family supervision, the practice of PA in girls was also positively associated with the frequency of meals had in company of their parents. However, just as with boys, insomnia and alcohol consumption were associated with increased PA practice. In the third article, the response variable was the prevalence of active adolescents (300+ minutes/week) in the Brazilian capitals, obtained by the accumulated physical activity indicator reported in PeNSE/2012. The explanatory variables were obtained from several sources and represent an aggregate average of each capital. These variables were divided into five domains: Natural environment (temperature); socioeconomic and educational indicators (per capita income); infrastructure (percentage of households with a wheelchair ramp); urban violence (death rate by homicide); socio-cultural encouragement for PA practice (percentage of active adults in leisure). Multiple linear regression was used to identify the associated factors. The final model showed that lower temperature (β: - 0.46, CI: - 0.88, - 0.04), higher IDEB (β: 3.02, IC: 0.36, 5.67) (β: 0.25, CI: 0.04; 0.47) and higher percentage of active adults (β: 0.35; CI: 0.13; 0.57) in the cities, are associated with the increase in prevalence of physically active adolescents. Conclusions: There was a stabilization of the prevalence of physically active adolescents living in Brazilian capitals between the years of 2012 and 2015, which shows the need to reassess and expand the public policies that promote PA. At the individual level, maternal schooling, healthy eating habits and family supervision have been associated with regular PA practice among adolescents, which evinces the importance of family in the acquirement of healthy habits by this age group. When analyzing contextual characteristics, it was verified that mild temperatures, higher quality of education, better infrastructure and greater socio-cultural support for PA are associated with increased proportions of active youths. Such results may contribute to the evaluation and implementation of more assertive public policies aiming at the increase of physical activity in Brazilian adolescents.